Recycled light-weight construction materials and their effect on electricity consumption in low-cost housings - Borbón Almada, Ana Cecilia; Alpuche Cruz, María Guadalupe; Miranda Pasos, Israel; Marincic Lovriha, Irene; Ochoa de la Torre, José Manuel (Acta Universitaria, 2019)
An efficient architecture is an integral part of sustainable development; therefore, it should include an envelope able to adapt to the climate and the constructive resources of the region. The evaluation of the thermal behavior of buildings by dynamic simulation is used worldwide to evaluate the energy efficiency of buildings. In Mexico, there is a lack of data on the thermal properties of the construction materials. In this paper, the thermal conductivity, specific heat and volumetric density of local construction materials, such as red common brick, light-weight block, natural cement-sand mortars, and recycled cement-sand mortars, made with recycled materials of concrete demolition, are obtained experimentally. The simulation results obtained show a decrease in the heat gains in walls and in the electricity consumptions for cooling. The decrease is over 8% when constructive systems conformed by lightened and recycled materials are used.